Chikungunya E2 Protein Produced in E. coli and HEK293-T Cells—Comparison of Their Performances in ELISA - Flávia Fonseca Bagno; Lara Carvalho Godói; Maria Marta Figueiredo; Sarah Aparecida Rodrigues Sérgio; Thaís de Fátima Silva Moraes; Natália de Castro Salazar; Young Chan Kim; Arturo Reyes-Sandoval; Flávio Guimarães da Fonseca (Viruses, 2020)
Chikungunya virus (CHIKV) is a mosquito-borne pathogen that causes a disease characterized by the acute onset of fever accompanied by arthralgia and intense joint pain. Clinical similarities and cocirculation of this and other arboviruses in many tropical countries highlight the necessity for efficient and accessible diagnostic tools. CHIKV envelope proteins are highly conserved among alphaviruses and, particularly, the envelope 2 glycoprotein (CHIKV-E2) appears to be immunodominant and has a considerable serodiagnosis potential. Here, we investigate how glycosylation of CHIKV-E2 affects antigen/antibody interaction and how this affects the performance of CHIKV-E2-based Indirect ELISA tests. We compare two CHIKV-E2 recombinant antigens produced in different expression systems: prokaryotic-versus eukaryotic-made recombinant proteins. CHIKV-E2 antigens are expressed either in E. coli BL21(DE3)—a prokaryotic system unable to produce post-translational modifications—or in HEK-293T mammalian cells—a eukaryotic system able to add post-translational modifications, including glycosylation sites. Both prokaryotic and eukaryotic recombinant CHIKV-E2 react strongly to anti-CHIKV IgG antibodies, showing accuracy levels that are higher than 90%. However, the glycan-added viral antigen presents better sensitivity and specificity (85 and 98%) than the non-glycosylated antigen (81 and 71%, respectively) in anti-CHIKV IgM ELISA assays.